#TITLE_ALTERNATIVE# - PRASETYA (NIM : 17302041); Dosen Pembimbing : Drs. Andriyanto Wibisono, M.Sn., EDWARD
We could see the character from a culture by seeing and paying close attention to the cultural product, one of them was traditional music. Indonesia have a large amount of traditional music types based on the art, that shows Indonesia was very rich in traditional culture. However in the middle of the development flow of technology and the change in time, lots of traditional music types disappeared and associated with the outside culture, especially in West Java. It is unfortunate that when a so heterogenous cultural product and had the typical characteristics as the identity of a nation was lost just like that. Bandung as one of the biggest cities in West Java had several facilities that could give knowledge about West Javanese tradition music, however the existence of these facilities was felt did not give the answer to the interest reduction of the community in traditional music. Apart from the human factor, many factors that caused traditional music were not all that paid attention to by the community, one of them was the shortage of facilities that could give knowledge about traditional music to the modern community that was general against the traditional music personally. Based on that reality, the existence of facilities where the modern community and the traditional could appreciate was really needed in the Bandung city. Moreover the existence of these facilities could reinforce the identity of the nation.